2021
DOI: 10.1177/10497323211003059
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Bereavement and Resilience in Refugee Resettlement: A Photovoice Study With Yazidi Women in the Midwest United States

Abstract: This study explored how ethnic Yazidi refugee women overcome adversity to promote psychosocial health and well-being within the context of U.S. resettlement. Nine Yazidi women participated in two small photovoice groups, each group lasting eight sessions (16 sessions total). Women discussed premigration and resettlement challenges, cultural strengths and resources, and strategies to overcome adversity. Yazidi women identified trauma and perceived loss of culture as primary stressors. Participants’ resilience p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…The majority of the participants were female (57.21%, n = 5,748) and the age range of the participants across all studies ranged from 18–68 years. The participants originated from more than 30 countries including Afghanistan [ 65 , 111 , 112 ], Congo [ 104 ], Eritrea [ 34 , 113 ], Iran [ 73 , 85 ], Iraq [ 60 , 81 , 85 , 105 , 114 ], Somalia [ 39 , 115 , 116 ], and Syria [ 38 , 51 , 53 , 54 , 73 , 90 , 94 , 95 , 101 , 108 , 111 , 117 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the participants were female (57.21%, n = 5,748) and the age range of the participants across all studies ranged from 18–68 years. The participants originated from more than 30 countries including Afghanistan [ 65 , 111 , 112 ], Congo [ 104 ], Eritrea [ 34 , 113 ], Iran [ 73 , 85 ], Iraq [ 60 , 81 , 85 , 105 , 114 ], Somalia [ 39 , 115 , 116 ], and Syria [ 38 , 51 , 53 , 54 , 73 , 90 , 94 , 95 , 101 , 108 , 111 , 117 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to social support, 28.3% of the studies in the review noted building and strengthening community networks was beneficial for psychological wellbeing, life satisfaction, and resettlement [20,27,34,45,47,50,51]. Notably, Remennick's work [52,53] and Tippens et al [24] demonstrate how support from co-ethnic communities significantly boosts the psychological well-being and health of older women.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies simply reported the participants were above a certain age. For example, two studies reported participants were 18 years and over [23,24]. One study recruited only elders aged 60 years and older [18].…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…Weng and Lee (2016) noted the importance of ethnic community in cultural maintenance and in extending familial and fictive kin networks. Additionally, organizational-level structures such as refugee resettlement agencies and ethnic community-based organizations (ECBOs) play a critical role in enhancing sense of community via social support or peer groups, activity nights, cultural celebrations, and resource-sharing events (Badali et al, 2017; Dubus, 2017; Keel & Drew, 2004; Tippens et al, 2021). Our application of the “coping reservoir” in tandem with the sense of community theory enabled us to explore macro-, meso-, and micro-inputs related to burnout and resilience as well as unpack how riCHWs navigated resources from multiple communities of belonging to enhance their self-efficacy and capacity to support their communities during the first year of COVID-19.…”
Section: Theoretical Frameworkmentioning
confidence: 99%